An analysis of the performance of Regional Development Banks (RDB) in Indonesia: Stochastic frontier analysis approach - Ferdian Timur Satyagraha; Rudi Purwono; Dyah Wulan Sari (Economies, 2022)
The dominance of the banking sector shows that the banking industry plays an important role in driving the economy in Indonesia. As part of the national banking industry, Regional Development Banks (RDB) are required to contribute to the economy through optimal performance. One of the important indicators in measuring company performance, including in the banking industry, is the level of efficiency. Efficiency in the banking industry can be observed from a micro and macro perspective, which leads to the ability of banks to survive in conditions of increasingly fierce competition in technology-based products and services, as well as the ability of banks to allocate financial resources to increase investment activities that can stimulate the economy. Therefore, this study examined the level of cost and profit efficiency of the RDB industry in Indonesia for the 2011-2020 period, as well as the internal and external variables that affect RDB inefficiency using Stochastic Frontier Analysis (SFA). The results show that there are no RDB's efficient in cost and profit. Furthermore, the variables capital adequacy ratio and technology investment impact on increasing cost and profit efficiency, opposite with non-performing loan. Therefore, to optimize the xRDB's cost and profit efficiency, the main thing that must be done includes managing and improving good quality loans as well as optimizing idle funds.
Keywords: 330; cost efficiency; profit efficiency; Regional Development Bank (RDB); SFA